The use of transgenic Plasmodium berghei expressing the Plasmodium vivax antigen P25 to determine the transmission-blocking activity of sera from malaria vaccine trials. - Ramjanee, S; Robertson, J; Franke-Fayard, B; Sinha, R; Waters, A; Janse, C; Wu, Y; Blagborough, A; Saul, A; Sinden, R (2007)
P25 is a major surface protein of Plasmodium ookinetes. Antibodies against P25 prevent the formation of oocysts in the mosquito and thereby block transmission of the parasite through an endemic population. Plasmodium vivax transmission-blocking vaccines based on Pv25 have undergone human trials and inhibit transmission significantly. The current assay to determine transmission-blocking activity (TBA) of these sera, the 'standard membrane feeding assay', is complex and can be performed by few groups worldwide that require both mosquito breeding facilities and access to volunteers naturally infected with P.vivax--a costly, and uncontrolled source of parasites. Here we report the development of novel assays to determine TBA using two clones (Pv25DR and Pv25DR3) of transgenic rodent parasites (Plasmodium berghei) expressing Pv25. We show that oocyst development of the transgenic parasites is inhibited by monoclonal antibody against Pv25 with the same kinetics exhibited by wild type parasites when exposed to mouse monoclonal antibodies targeted to a paralogous protein P28. Human transmission-blocking sera from a clinical vaccine trial of Pv25 inhibited oocyst development of Pv25DR and Pv25DR3, whereas non-blocking sera did not. We further show transmission-blocking activity can be determined in a simple assays of ookinete development in vitro, assays that obviate the need for mosquito colonies. These results demonstrate that transgenic rodent malarias expressing proteins from human Plasmodium species can be cheap, safe, and simple tools for testing TBA from sera. To this end the cloned lines have been deposited with, and are freely available from, MR4.